Semantic communication accelerates the integration of network and information processing - SUN Yihao; JIANG Sheng; ZHOU Xu; LEI Bo; JIANG Lintao (Dianxin kexue)
As a new communication paradigm, semantic communication can differentiately extract and transmit task-related semantic information to improve network efficiency. However, semantic communication requires the network to actively participate in information processing, provide computing and storage resources, and at the same time requires the network to have the ability to perceive the importance of information and its own resource conditions. The development path of the integration of network and information processing was discussed. Fisrtly, the evolution of network capabilities and the development history of semantic communication were introduced. Then, how the network transformed from a simple data transmission pipeline to an information processing platform was analyzed from three aspects: firstly, task-oriented semantic communication can extract semantic information according to intelligent task requirements; secondly, the network supports the training, storage and reasoning of semantic communication models by scheduling cloud-edge resources; thirdly, the coordinated evolution of network and semantic communication enables semantic communication to understand the network status, and the network has the ability to intelligently respond to needs of semantic communication. Finally, typical application scenarios of the integration of network and information processing were introduced.